ANALISIS PENGARUH BIAYA OPERASIONAL PADA PERUSAHAAN PENERBANGAN NASIONAL - Dheny Biantara (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2017)
Summarized Indonesian airline executive views on the reason for the cost problem in mayor airline and on the potential areas and measures of cost reduction in airline operation. Present an introduction survey where 3 executives from 3 Indonesian airlines were respondent. In the executive opinion the cost problem in mayor Indonesian airline is primarily due to fuel and oil pricing and money currency. Of the various function in airline maintenance was seen as least cost efficiency, whereas flight operation was seen as an area with most potential for cost reduction. Indonesian airline had made route and fleet changes after the beginning of 2011 to reduce cost, concludes from the analisys result having privatization would be an important step towards more efficient airline operation. Flexibility from Indonesian airline regulatory would be very much welcome and the value chain concept to improve Indonesian airline having competitive adventage and cost leadership differentiation